Literacy and Self Regulation to Overcome Social Media Addiction in Z Generation - Rizki Briandana; Nindyta Aisyah Dwityas; Mohamad Saifudin Mohamad Saleh (Universitas Mercu Buana, 2023)
Social media platforms today allow people to communicate with anybody, anywhere, and at any time. Social media not only has a beneficial impact but also a harmful one. Users that use social media excessively may develop addiction, which is closely tied to one's mental health. Self-regulation has been found to negatively impact social media addiction in previous studies, although this particular study only included high school students. Thus, the goal of this civic duty is to ascertain how self-control affects social media addiction among Generation Z students. The offline portion of this activity will be done in association with Universiti Sains Malaysia. 54 people from SMK 60 Jakarta participated in this activity on March 15, 2023. These actions were posted on JPNN and Rakyat Merdeka online Media.